Jaina sampradāya meṃ moksha, avatāra, aura punarjanma : tīna vyākhyāna - Jaini, Padmanabh S. (Śāha Popaṭalāla Hemacanda adhȳtma vyākhyānamālā ;, 1982)
Transcript of lectures on the Jaina viewpoint on salvation, incarnation, and reincarnation.